Handbook of experimental methods for process improvement - Drain, David (Chapman & Hall, 1997)
Presented in a clear and organized manner, this handbook shows engineers how to apply sophisticated statistical and experimental design methods to improve industrial and manufacturing processes. Throughout the text, concepts are developed in the context of industrial examples and the use of software is made readily accessible to promote a better understanding through graphical and statistical analysis.